The effect of crumb rubber modifier to the properties and rheological behaviour of asphalt binder / Nuha S. Mashaan - Nuha S., Mashaan (2012)
Several road pavement distresses are related to bitumen properties. Rutting and fatigue cracking are major distresses that lead to permanent failure in pavement construction. The increased use of crumb rubber modifier in flexible pavements justifies the necessity for a better understanding of its physical and rheological characteristics as well as its elasticity behaviour. Basically the performance and properties of rubberised bitumen binder are influenced by the blending conditions and crumb rubber modifier content. Thus, the main objective of this research is to investigate the effect of blending time, blending temperature and crumb rubber content on the performance properties of rubberised bitumen binders. In addition, this research aims to investigate the effect of crumb rubber modifier concentration on the rheological and physical properties of rubberised bitumen after short- term aging and long- term aging. Laboratory investigation has been conducted on asphalt binder properties as a function of various blending temperatures, blending times and different crumb rubber modifier (CRM) percentages. Twenty CRM binder combinations (2 blending times, 2 blending temperatures and 5 CRM percentages by weight of binder) have been prepared as test samples and evaluated. Six different binder tests have been conducted. Namely (penetration test, Brookfield viscosity test, dynamic shear rheometer test (DSR), ductility test, elastic recovery test and softening point test). In order to evaluate the durability performance of rubberised bitumen, aging tests have been conducted using short-term aging (i.e., rolling thin film oven test or RTFOT) and long-term aging (i.e., pressure aging vessel or PAV). The results of this study showed that crumb rubber content and blending temperature for rubberised bitumen binders have a significant effect on modified binder properties while the blending time showed insignificant effect on modified bitumen binder properties in the case of 30 and 60 minutes. Higher blending temperature for rubberised bitumen binder resulted in an increase in viscosity, complex shear modulus, softening point, elastic recovery and softening point as well as a decrease in penetration, phase angle and ductility. Statistical analysis using two-way ANOVA showed that CRM is statistically significant in terms of increasing penetration of asphalt binder, elasticity, viscosity, rutting factor G*/ sin (δ) at 76 °C and resistance to flow. Moreover, the results showed that the use of rubberised bitumen binder reduced the aging effect on physical and rheological properties of the bitumen binder as illustrated through lower aging index of viscosity, an increase in G*/ sin δ at 76 ⁰C, a decrease in phase angle (δ) with increased crumb rubber modifier content, indicating that the crumb rubber might improve the oxidative aging resistance of rubberised bitumen binder. In addition, the results show that the softening point increment (ΔS) and penetration aging ratio (PRA) of the rubberised bitumen binder decreased significantly due to crumb rubber modification. Furthermore, the higher crumb rubber content, the lower G* sin δ at 31 ⁰C after PAV aging, thus leading to higher resistance to fatigue cracking.